Analysis of total productive maintenance application as productivity support with overall equipment effectiveness measurement - Ririn Novianti; Ardi Paminto; Doddy Adhimursandi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2022)
This research aims to measure the value of the effectiveness of equipment, find the root causes of problems and provide suggestions for improvement. The study was conducted on a Rotary Lathe machine, which has a high enough breakdown rate. This research begins by measuring the achievement of overall equipment effectiveness (OEE) values, then identifying the six big losses that occur. The results showed that the average OEE value on the Rotary Lathe machine was 80.17%. The value of this effect was not yet reached the ideal conditions for world-class companies ideally is 85%.Â  The most significant factors that make the score of OEE has not been reached ideally are the number of Six Big Loses percentage on idling and minor stoppages for 53.44%, and setup and adjustment for 41.75% of all-time loss.The proposed corrective actions are to increase the preventive maintenance activities on the production machine, determine the standard setup on the machine, conduct training programs for workers and operators periodically, clean the machine and work area before and after the operation process and provide repair tools as needed.